The Impact Of Cyber Espionage Issue On Maritime Security Cooperation Between Indonesian National Police And Australian Federal Police - Muhamad Rizal Aria Sandy; Abdul Rivai Ras; Yusnaldi Yusnaldi; Pujo Widodo; Panji Suwarno (CV. AFDIFAL MAJU BERKAH, 2023)
In international law, espionage committed by one country against another in the form of wiretapping is a form of violation of international law and can disrupt relations between the two countries concerned. In this case, Australia had wiretapped Indonesian executive officials such as the President and his deputy in 2013. The action caused the intensity of the relationship between Indonesia and Australia to heat up. In this case, the geographical proximity between Indonesia and Australia causes the two countries to need each other, especially in dealing with cross-border crimes involving the two countries. This research intends to find out how the influence of Australia's wiretapping actions in Indonesia to the bilateral cooperation in handling transnational crimes. This research will use Butler's conflict management theory to examine the resolution of the conflict and how the resolution affects the cooperation between the two countries. From this research, it is known that the actions taken by Australia made the relationship between Indonesia and Australia tense. This was followed by the termination of bilateral cooperation projects between Indonesia and Australia. One of the areas of discontinued cooperation is cooperation in combating transnational crimes between the Indonesian National Police (Polri) and the AFP. This situation will create a loophole for perpetrators of cross-border crimes in carrying out their actions between the two countries, one of the most vulnerable transnational crimes is related to people smuggling. This affects the maritime security sector between the two which must be anticipated immediately.